Recent Advances in Mono‐ and Difunctionalization of Unactivated Olefins. Issue 12 (23rd November 2021) - Patel, Monak; Desai, Bhargav; Sheth, Aakash; Dholakiya, Bharatkumar Z.; Naveen, Togati
Abstract: Olefins are synthetically useful building blocks in modern organic synthesis. Direct functionalization of olefins; represent one of the most explored transformations in synthetic chemistry due to their easy availability and reactivity towards large number of reactants affording diverse range of organic compounds. In recent times, the development of new protocols for the functionalization of olefins is a growing realm. A plethora of olefin functionalization methodologies have been reported in the literature through ionic and free radical mechanisms including single electron transfer (SET) in the last two decades. This review gives an overview of mono‐ and difunctionalization of unactivated olefins, with an emphasis on the mechanistic details. Abstract : Direct functionalization of olefins represent one of the most explored transformation in organic synthesis. This review highlights the most recent breakthroughs in the mono‐ and difunctionalization of unactivated olefins.